Pediatric multiple sclerosis: Improving outcome through high-efficacy therapies - Lama Saleh Aljomah; E. Ann Yeh (Neurotherapeutics)
Pediatric-onset multiple sclerosis (POMS) refers to multiple sclerosis occurring in individuals under 18 years of age. It is characterized by poor cognitive outcomes and a more inflammatory course, more frequent clinical relapses, and a greater number of MRI lesions compared to adult-onset MS (AOMS). Prompt recognition of multiple sclerosis in this population is essential, as early intervention with disease-modifying therapies may change the trajectory of disease progression. In this paper, we will review diagnostic criteria for pediatric multiple sclerosis, differential diagnosis, and current and emerging therapeutic approaches. While a number of DMTs are approved for adult MS, few are approved for pediatric use. Many of these DMTs are used off-label, with real-world evidence demonstrating their effectiveness and safety. The review evaluates existing evidence for the use of these therapies in pediatric populations, with an emphasis on both existing clinical trials and real-world data that supports their use. In addition, we will briefly highlight ongoing clinical trials and emerging therapies for POMS.